Analisis Pengaruh Pengangguran dan Inflasi Terhadap Pertumbuhan Ekonomi Di Indonesia: (Studi Kasus Di Sumatera Utara) (Jurnal Riset Manajemen dan Akuntansi, 2025)
Economic growth is an important indicator that reflects the success of development in a region, where the results of this growth are expected to be enjoyed by all layers of society and the government. North Sumatra, with its abundant natural and human resources, has great potential for continued development. This study aims to analyze the impact of unemployment and inflation on economic growth in North Sumatra during the period of 2017-2023. The method used in this research is quantitative research employing multiple linear regression analysis. The data used are secondary data for the period of 2017-2023 obtained from the Central Statistics Agency (BPS) of North Sumatra. The research variables include Unemployment (X1), Inflation (X2), and Economic Growth (Y), with statistical tests conducted using SPSS 20 software. The results obtained from this study indicate that the unemployment variable has a significant effect on economic growth with a value of 0.002 < 0.05, while the inflation variable does not have a significant effect on economic growth with a value of 0.091 > 0.05. The simultaneous test of the unemployment and inflation variables through the F-test shows a significant value of 0.005 < 0.05, indicating that unemployment and inflation together have a significant impact on economic growth.